Moderating Religion, Bridging Cultures: The Impact of Pesantren Riyadul 'Ulum Wadda'wah on Intercultural Harmony - Mohammd Ridwan; Joni Ahmad Mughni; Muhammad Abdul Muiz (Indonesian Journal of Islamic Religious Education, 2025)
This research explores the application of religious moderation in building intercultural harmony in the social dynamics of the Pesantren Riyadul 'Ulum Wadda'wah community in Tasikmalaya, Indonesia. Using a qualitative approach, this study examines the interactions among santri who come from various cultural backgrounds in a pesantren environment that integrates classical religious education, modern discipline, and pesantren values that uphold togetherness and tolerance. Data were collected through in-depth interviews, participatory observation, and document analysis. The results showed that Pesantren Riyadul 'Ulum Wadda'wah actively promotes intercultural harmony through teaching religious moderation values that emphasize the balance between spiritual and social life, integrating religious moderation in pesantren learning, and creating spaces for intercultural dialogue. The findings show that pesantren can function as cultural bridges and agents of social cohesion in multicultural communities. The integration of religious moderation values with symbolic interaction confirms the relevance of pesantren as pioneers in promoting intercultural harmony in the modern era.